Collapse of a country : a diplomat's memoir of South Sudan - Coghlan, Nicholas, 1954- (McGill-Queen's University Press, 2017)
The first Canadian diplomat to be posted to war-torn Sudan, Nicholas Coghlan was a natural choice to lead Canada's representation in the new Republic of South Sudan soon after the country was founded in 2011. In late 2013, Coghlan and his wife Jenny were in the capital, Juba, when it erupted in gunfire and civil war pitted one half of the army against the other, Vice-President Machar against President Kiir, and the Nuer tribe against the Dinka. This action-focused narrative, grounded by accounts of meetings with key leaders and travels throughout the dangerous, impoverished hinterland of South Sudan, explains what happened in December 2013 and why. In harrowing terms, Collapse of a Country describes the ebb and flow of the war and the humanitarian tragedy that followed, the Coghlans' scramble to evacuate South-Sudanese Canadians from Juba, and the well-meant but often ill-conceived attempts of the international community to mitigate the misery and bring peace back to a land that has rarely known it. Coghlan's stark narrative serves as a lesson to politicians, diplomats, aid workers, and practitioners on the breakdown of governance and relationships between ethnic groups, and the often decisive role of international development representatives. Fast-paced and poignant, Collapse of a Country gives an insider's glimpse into the chaos, violence, and ethnic conflicts that emerged out of a civil war that has been largely ignored by the West.